Challenges in Treating Statin-Associated Necrotizing Myopathy - Patrick Webster; Nicholas Wiemer; Abdalhamid Al Harash; Cody Marshall; Nazia Khatoon; Michael Lucke (Case Reports in Rheumatology)
Myalgia and mild elevation in muscle enzymes are common side effects of statin therapy. While these symptoms are generally self-limited, in rare cases, statin use is associated with an immune-mediated necrotizing myopathy caused by development of autoantibodies against HMG-CoA reductase. The primary presenting symptom of this condition is progressive symmetric proximal weakness that does not abate or worsens even after cessation of statin therapy and is associated with markedly elevated creatine kinase (CK) levels. To date, no randomized controlled trials have been conducted to identify the most effective treatment for statin-associated autoimmune myopathy. Treatment recommendations involve a combination of steroids and immunosuppressive drugs. This single-center case series highlights the clinicopathologic features diagnostic for statin-associated autoimmune myopathy as well as treatment challenges for the patient population. The series highlights a range of potential presentations, from mildly symptomatic despite highly elevated CK, to severe muscle weakness including dysphagia. Multiple patients required several immunosuppressant medications as well as intravenous immunoglobulin (IVIG) to achieve disease control. In this case series, marked improvement was noted in several diabetic patients with IVIG.